Visual Design Of Commercial Campaign “Grow With Nature” For Kemaiu Haircare Promotion - Khansa Maritza Isnaen; Aditya Rahman Yani; Widyasari Widyasari (QISTINA: Jurnal Multidisiplin Indonesia, 2026)
This study aims to increase public awareness about the importance of maintaining healthy hair naturally and as a promotional optimization strategy for Kemaiu shampoo products. Data collection was carried out using observation, interviews, and questionnaires. While the method in this design uses design thinking which includes the AISAS (Attention, Interest, Search, Attention, Share) communication technique. The design of the campaign visual design through digital media is expected to be beneficial in terms of functional, emotional and life changing. The results of the study are elements and components of design visualization used in Kemaiu's commercial campaign regarding the importance of maintaining healthy natural hair.